The carbon footprint of behavioural support services for smoking cessation. Issue 5 (12th March 2013) - Smith, Anna Jo Bodurtha; Tennison, Imogen; Roberts, Ian; Cairns, John; Free, Caroline
Abstract : Objective: To estimate the carbon footprint of behavioural support services for smoking cessation: text message support, telephone counselling, group counselling and individual counselling. Design: Carbon footprint analysis. Data source: Publicly available data on National Health Service Stop Smoking Services and per unit carbon emissions; published effectiveness data from the txt2stop trial and systematic reviews of smoking cessation services. Main outcome measures: Carbon dioxide equivalents (CO2 e) per 1000 smokers, per lifetime quitter, and per quality-adjusted life year gained, and cost-effectiveness, including social cost of carbon, of smoking cessation services. Results: Emissions per 1000 participants were 8143 kg CO2 e for text message support, 8619 kg CO2 e for telephone counselling, 16 114 kg CO2 e for group counselling and 16 372 kg CO2 e for individual counselling. Emissions per intervention lifetime quitter were 636 (95% CI 455 to 958) kg CO2 e for text message support, 1051 (95% CI 560 to 2873) kg CO2 e for telephone counselling, 1143 (95% CI 695 to 2270) kg CO2 e for group counselling and 2823 (95% CI 1688 to 6549) kg CO2 e for individual counselling. Text message, telephone and group counselling remained cost-effective when cost-effectiveness analysis was revised to include the environmental and economic cost of damage from carbon emissions. Conclusions: All smoking cessation services had low emissions compared to the health gains produced. Text message support had the lowest emissions of the services evaluated. Smoking cessation services have small carbon footprints and were cost-effective after accounting for the societal costs of greenhouse gas emissions.